2006
DOI: 10.2139/ssrn.895270
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rail Transport on Real Estate Prices: An Empirical Analysis of the Dutch Housing Market

Abstract: A hedonic pricing model is estimated to analyse the impact of railways on house prices in terms of distance to railway station, frequency of railway services and distance to the railway line. Correcting for a wide range of other determinants of house prices we find that dwellings very close to a station are on average about 25% more expensive than dwellings at a distance of 15 kilometres or more. A doubling of frequency leads to an increase of house values of about 2.5%, ranging from 3.5% for houses close to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 17 publications
3
93
1
4
Order By: Relevance
“…Andersson et al (2010) studied the effects of accessibility to high speed rail in Taiwan and discovered that overall it had a very minor effect on property prices. This clearly contrasts with the results of Debrezion et al (2006) in Holland, where the effects of proximity to a railways station were more than double those found in Taiwan. Banister and Thurstain-Goodwin (2011) found that, at the microlevel, non-transport benefits provided by investment in railways can be seen in the land and property markets.…”
Section: Bibliographic Reviewcontrasting
confidence: 97%
“…Andersson et al (2010) studied the effects of accessibility to high speed rail in Taiwan and discovered that overall it had a very minor effect on property prices. This clearly contrasts with the results of Debrezion et al (2006) in Holland, where the effects of proximity to a railways station were more than double those found in Taiwan. Banister and Thurstain-Goodwin (2011) found that, at the microlevel, non-transport benefits provided by investment in railways can be seen in the land and property markets.…”
Section: Bibliographic Reviewcontrasting
confidence: 97%
“…There is a general consensus in the literature about the betterment effect of public transit with regard to the nearby urban residential properties, as the positive externalities of transportation infrastructure are known to be capitalized in property price (Bowes and Ihlanfeldt, 2001, Debrezion et al, 2011, Hess and Almeida, 2007, Ryan, 1999. However, relatively fewer transportation studies have managed to differentiate between the uplift of property value due to actual improvement in transport accessibility versus the real estate investors' speculation on future capital gains through transit-induced property value appreciation.…”
Section: Introductionmentioning
confidence: 99%
“…Highway accessibility can reduce transportation costs (Forkenbrock, 1990) and generally has a positive effect on housing prices (Levkovich et al, 2016). However, the effect differs slightly as location varies because the peak effect usually occurs when a property is located 4 to 5 km from a highway access point (Debrezion et al, 2005). Therefore, we propose the following hypothesis.…”
Section: Hypothesismentioning
confidence: 94%
“…Furthermore, the house value can decrease as a property is located farther away from a station (Hewitt and Hewitt, 2012) or increase because of reduced noise and pollution (Debrezion et al, 2005). Highway accessibility can reduce transportation costs (Forkenbrock, 1990) and generally has a positive effect on housing prices (Levkovich et al, 2016).…”
Section: Hypothesismentioning
confidence: 99%